A novel strategy for controllable electrofabrication of molecularly imprinted polymer biosensors utilizing embedded Prussian blue nanoparticles - Bahareh Babamiri; Mohammadreza Farrokhnia; Mehdi Mohammadi; Amir Sanati Nezhad (Scientific Reports)
Abstract The reproducibility of ultrasensitive biosensors is vital for clinical research, scalable manufacturing, commercialization, and reliable clinical decision-making, as batch-to-batch variations introduce significant uncertainty. However, most biosensors lack robust quality control (QC) measures. This study introduces an innovative QC strategy to produce highly reproducible molecularly imprinted polymer (MIP) biosensors by leveraging real-time data from the electrofabrication process. Prussian Blue nanoparticles (PB NPs) embedded within the MIP structure enable precise monitoring of surface properties, conductivity, MIP film thickness, and template extraction efficiency. The QC strategy utilizes variations in the current intensity of PB NPs during fabrication to implement real-time, non-destructive QC protocols at critical fabrication stages, minimizing measurement variability and ensuring consistency. This approach was validated by fabricating MIP biosensors for detecting agmatine metabolite and glial fibrillary acidic protein (GFAP) in phosphate-buffered saline (PBS). The QC strategy reduced relative standard deviation (RSD) by 79% for agmatine (RSD = 2.05% QC, RSD = 9.68% control) and 87% for GFAP (RSD = 1.44% QC, RSD = 11.67% control). Moreover, quality-controlled biosensors achieved success rates of 45% for agmatine and 36% for GFAP detection, significantly outperforming bare screen-printed electrodes. This work marks a significant advancement in biosensor development by integrating robust QC protocols directly into the fabrication process. By embedding PB NPs and monitoring electrochemical signals in real-time, this strategy delivers an unprecedented level of reproducibility, scalability, and reliability for MIP biosensors, addressing critical challenges in point-of-care diagnostics and commercial applications.